Soliton dynamics in optical fiber based on nonlinear Schrödinger equation. Issue 3 (March 2023) - Abdillah Mardi, Harish; Nasaruddin, Nasaruddin; Ikhwan, Muhammad; Nurmaulidar, Nurmaulidar; Ramli, Marwan
Abstract: Optical fiber is a component of the green and sustainable internet. This paper analyzes the energy loss induced by the attenuation effect of electromagnetic waves during optical fiber propagation. The dynamics of the Hamiltonian, which was derived using the dynamics of the solution the Nonlinear Schrödinger equation (NLS) problem, were used to investigate the energy drop. In this study, the Newton-Raphson (NR) approach was used to establish the stationary solution of the NLS problem, and the fourth order Runge-Kutta method was used to evaluate the dynamics of the solution (RK4). In this study, numerous parameters are adjusted, including group wave dispersion, nonlinearity, attenuation parameter, and potential trap. The solution of the NR approach is fairly close to the analytical solution based on the analytical solutions. The dynamics of the NLS equation solution are greatly influenced by parameters. The obtained results reveal that for large attenuation parameter values, the strength of the propagating electromagnetic waves decreases quite quickly. The result also shows that the other parameters studied must be maintained at the best conditions to support the attenuation parameters and potential trap. This condition is an indicator in the choice of the fundamental material for producing optical fiber, which should have a low attenuation and dispersion effect.